Hal Hadzihi ‘Alamah: Semiotika Cinta Nizar untuk Balqis - Muhammad Hasyim; Misbahus Surur; Nur Hasaniyah; Durrotun Humaira (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2026)
This study aims to analyze the matrix and trace the hypogram of the poem Hal Hādhihi ‘Alāmah by Nizar Qabbani through the perspective of Michael Riffaterre’s semiotic theory. The analysis focuses on poetic symbols and expressions of ungrammaticality (indirection) as key mechanisms in the construction of meaning. Employing a qualitative descriptive approach, data were collected through close reading, while analysis was conducted using Riffaterre’s dual reading model, namely heuristic and hermeneutic readings. The study examines selected stanzas that display patterns of symbolic repetition, metaphorical language, poetic diction, and pronoun usage associated with the representation of a female figure. The findings indicate that the matrix of the poem centers on the figure of sayyidatī (سَيِّدَتِيْ), which is actualized through various linguistic models in the form of words, expressions, and poetic imagery that consistently refer to an idealized woman. The potential hypogram is represented by the figure of sayyidatī and its lexical variants, such as anti (أَنْتِ), unṡāyā (أُنْثاَيَ), and dumyyah (دُمْيةٌ), while the actual hypogram refers to Balqis al-Rawi, the poet’s wife, as well as to an intertextually related poem within the same anthology, Hal Ya‘rifu al-Qurrā’?. This study demonstrates that Riffaterre’s semiotic framework is effective in revealing the latent structure of meaning in Qabbani’s romantic poetry through the systematic relationship between matrix, model, and hypogram. Abstrak Penelitian ini bertujuan menganalisis matriks dan melacak hipogram dalam puisi Hal Hādhihi ‘Alāmah karya Nizar Qabbani melalui perspektif semiotika Michael Riffaterre. Kajian ini berfokus pada simbol-simbol puitik dan ungkapan yang mengandung ketidaklangsungan ekspresi (ungramatikalitas) sebagai mekanisme utama pembentukan makna. Penelitian menggunakan metode kualitatif-deskriptif dengan teknik pembacaan cermat, sementara analisis data dilakukan melalui pembacaan ganda Riffaterre, yakni pembacaan heuristik dan hermeneutik. Analisis dibatasi pada bait-bait utama yang menunjukkan pola repetisi simbolik, penggunaan metafora, diksi puitik, dan kata ganti yang merepresentasikan figur perempuan. Hasil penelitian menunjukkan bahwa matriks puisi berpusat pada sosok sayyidatī (سَيِّدَتِيْ), yang dimanifestasikan melalui berbagai model linguistik berupa kata, ungkapan, dan citraan puitik yang mengarahkan makna pada figur perempuan ideal. Hipogram potensial puisi ini berupa representasi sosok sayyidatī beserta variasi leksikalnya, seperti anti (أَنْتِ), unṡāyā (أُنْثاَيَ), dan dumyyah (دُمْيةٌ), sedangkan hipogram aktualnya merujuk pada figur Balqis al-Rawi, istri penyair, serta keterkaitannya dengan puisi lain dalam antologi yang sama, yaitu Hal Ya‘rifu al-Qurrā’?. Penelitian ini menegaskan bahwa semiotika Riffaterre efektif dalam mengungkap struktur makna laten puisi romantis Qabbani melalui relasi sistematis antara matriks, model, dan hipogram.